2007
DOI: 10.3844/jssp.2007.138.142
|View full text |Cite
|
Sign up to set email alerts
|

Old and Modern Construction Materials In Yemen: The Effect In Building Construction In Sana’a

Abstract: Sana'a city in Yemen is one of the oldest cities in the worlds, which has different forms of building built with different types of materials. In the present work, the old and new forms of building construction and the building materials used in Sana'a, the sources available for the new material, the effects of new material usage on building forms are all presented with the advantages and disadvantages of each material. The old shapes of buildings in Yemen and the classical and modern forms of construction usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 1 publication
3
7
0
Order By: Relevance
“…The high cost could also be due to using cement mortar to fill irregular empty spaces between adjacent stones. This finding is the same as the study conducted by Al‐Kahtani and Al‐Darzi (2007), which found that concrete blocks was the best choice available for low‐income people in Sana'a as the cost of stone was about ten times that of the concrete block.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The high cost could also be due to using cement mortar to fill irregular empty spaces between adjacent stones. This finding is the same as the study conducted by Al‐Kahtani and Al‐Darzi (2007), which found that concrete blocks was the best choice available for low‐income people in Sana'a as the cost of stone was about ten times that of the concrete block.…”
Section: Resultssupporting
confidence: 85%
“…“Traditional methods used” is ranked last implying that it is timely that method be replaced for better quality housing. According to Al‐Kahtani and Al‐Darzi (2007), using new building material such as concrete block appears to be the best choice available for the low‐income people in Yemen. Although the cost of stone building is about ten times more than concrete block, the use of these materials was still widely accepted because of the poor quality of concrete block.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To increase efficiency in the systems design process, the engineer (designer) can increase the probability that the first design(s) concept is close to optimum by recognizing that the unique environmental and socio‐economic conditions of a location will directly influence the physical characteristics of a house design. This section provides recommendations to help the designer concept a near optimum initial design alternative (Alaghbari et al , 2004; Salama, 2006; Al‐Kahtani and Al‐Darzi, 2007).…”
Section: Affordable Housing Designmentioning
confidence: 99%